Pembatalan Peraturan Daerah Nomor 15 Tahun 2014 di Kabupaten Natuna - Patros, Asmin; Dewi, Ratna Sari Duta (Journal of Law and Policy Transformation, 2016)
Regional Regulation (PERDA) is a political product that is formed by the Regional Government and the Parliament. Regional Government is divided into provincial government that has the authority to establish a Provincial Regulation is the Governor together with the Provincial Parliament. The District Governement that has the authority to establish a District Regulation is the Regency Head or Mayor together with the District Parliament. The regional regulations as Legal Product are a form of written law that contains the rules of behavior that are binding in general. The substance of Regional Regulation must be further elaborated  from the higher law by taking into account the specificity of each region. The Regulation must not contradict with higher laws and regulations and as well as public interest. The purpose of this study is to explain the establishment of the villages which is located in Natuna regency. It examines whether it has fulfilled the requirements that are regulated by the Law and to explain its legal implications. The data collection is obtained from study of documents and literature. The method used in this study is a normative legal research method. The results showed that the Establishment of Natuna Regency Regulation No. 15 of 2014 concerning the Establishment of the Village did not follow the procedures / mechanisms that are regulated in the Government Regulation, therefore the Riau Islands Governor has not issued a register code for Village Preparation Establishment, and Registration Number to regulate the village establishment.  Consequently, the Minister of the Interior has not issued Village codes.  Accordingly,  the Regional Regulation may be declared  as not aligning with the legal procedures. === Peraturan Daerah atau disingkat Perda merupakan produk politik hukum daerah yang dibentuk oleh Pemerintah Daerah dan DPRD. Dimana Pemerintah Daerah terbagi menjadi pemerintahan Provinsi yang memiliki kewenangan untuk membentuk Perda Provinsi adalah Gubernur bersama-sama dengan DPRD Provinsi. Sedangkan untuk pemerintahan Kabupaten/Kota yang memiliki kewenangan untuk membentuk Perda Kabupaten/Kota adalah Bupati/Walikota bersama-sama dengan DPRD Kabupaten/Kota. Peraturan Daerah sebagai produk hukum daerah merupakan bentuk hukum yang tertulis yang berisi aturan tingkah laku yang bersifat mengikat secara umum. Pengaturan Perda secara substansi haruslah merupakan penjabaran lebih lanjut dari peraturan perundang-undangan yang lebih tinggi tingkatannya, dengan memperhatikan kekhususan masing-masing daerah dan tidak bertentangan dengan peraturan perundang-undangan yang lebih tinggi serta kepentingan umum. Tujuan penelitian ini adalah untuk menjelaskan pembentukan desa-desa yang berada di Kabupaten Natuna apakah telah memenuhi persyaratan sebagaimana yang diatur dalam Peraturan Perundang-undangan dan untuk menjelaskan implikasi hukum. Pengumpulan data dilakukan dengan studi dokumen dan kepustakaan. Metode penelitian yang digunakan dalam penulisan ini adalah metode penelitian hukum Normatif. Hasil penelitian menunjukkan bahwa Penetapan Peraturan Daerah Kabupaten Natuna Nomor 15 Tahun 2014  tentang Pembentukan Desa yang tanpa melalui prosedur/mekanisme sebagaimana diatur di dalam Peraturan Perundang-Undangan sehingga Gubernur Kepulauan Riau tidak mengeluarkan Kode Register untuk Desa Persiapan, Nomor Registrasi untuk Peraturan Daerah dan Kode Desa oleh Menteri Dalam Negeri sehingga Peraturan Daerah tersebut dapat dinyatakan ?tidak mengikuti prosedur hukum yang berlaku?.